1996
DOI: 10.1038/nm0396-342
|View full text |Cite
|
Sign up to set email alerts
|

Lytic growth of Kaposi's sarcoma–associated herpesvirus (human herpesvirus 8) in culture

Abstract: Kaposi's sarcoma (KS) is the leading neoplasm of AIDS patients, and HIV infection is known to be a major risk factor for its development. However, KS can occur in the absence of HIV infection and the risk of KS development varies widely even among HIV-infected patients, with homosexual men with AIDS being 20 times more likely to develop KS than AIDS-afflicted children or hemophiliacs. These and other data strongly suggest that a sexually transmitted agent or co-factor may be involved in KS pathogenesis. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
854
3
14

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 970 publications
(897 citation statements)
references
References 24 publications
26
854
3
14
Order By: Relevance
“…DNA sequences from a Herpesvirus have recently been detected in both AIDSrelated and classical KS lesions (Su et al, 1995;Chang et al, 1994) and culturing of the virus has been reported (Renne et al, 1996). If involved in the aetiology of KS, differences in the prevalence of the virus with respect to time and place or in cofactors determining disease progression offer a plausible explanation for the observed geographic variation and the observed increase in KS incidence.…”
Section: Resultsmentioning
confidence: 99%
“…DNA sequences from a Herpesvirus have recently been detected in both AIDSrelated and classical KS lesions (Su et al, 1995;Chang et al, 1994) and culturing of the virus has been reported (Renne et al, 1996). If involved in the aetiology of KS, differences in the prevalence of the virus with respect to time and place or in cofactors determining disease progression offer a plausible explanation for the observed geographic variation and the observed increase in KS incidence.…”
Section: Resultsmentioning
confidence: 99%
“…15 Strong evidence that the infection of PEL cell lines with HHV-8 represents a true latent infection rather than an aberrant or 'dead end' infection came from experiments showing that a switch to productive (lytic) replication was induced in response to appropriate stimuli. 28 Indeed, BCBL-1 (HHV-8+ EBV-neg) exposed to phorbol ester TPA switched to productive (lytic) HHV-8 replication, whereas TPA did not induce this switch in BCBL-2 (HHV-8+ EBV+) raising the possibility that EBV may somehow interfere with HHV-8 induction. 28 Six PEL cell lines are co-infected with EBV, showing a monoclonal pattern of EBV infection (Figure 4b), whereas the remaining five cell lines are EBV-negative (Table 3, Figure 3) suggesting that EBV is not an absolute requirement for the establishment of the cell lines.…”
Section: Viral Statusmentioning
confidence: 99%
“…28 Indeed, BCBL-1 (HHV-8+ EBV-neg) exposed to phorbol ester TPA switched to productive (lytic) HHV-8 replication, whereas TPA did not induce this switch in BCBL-2 (HHV-8+ EBV+) raising the possibility that EBV may somehow interfere with HHV-8 induction. 28 Six PEL cell lines are co-infected with EBV, showing a monoclonal pattern of EBV infection (Figure 4b), whereas the remaining five cell lines are EBV-negative (Table 3, Figure 3) suggesting that EBV is not an absolute requirement for the establishment of the cell lines. 8 Furthermore, most EBV+ cell lines display a restricted EBV antigen profile being negative for EBNA-2 and LMP-1 expression, two EBV-encoded transforming antigens.…”
Section: Viral Statusmentioning
confidence: 99%
“…This raises the possibility that inhibition of HDACs may reactivate latent proviruses. Indeed, HDAC6 inhibitors, as well as other HDACs, are subsequently found to reactivate HIV [141][142][143][144], EpsteinBarr virus [145][146][147], Kaposi's sarcoma-associated herpesvirus (KSHV) [148,149] and feline immunodeficiency virus [150].…”
Section: Hdac6 Controls Viral Lytic-latency Switchmentioning
confidence: 99%